Establecimiento de las Auditorias mensuales a las prestaciones de alimentos recaudadas a través de la ley - Jara Minga, Tatiana Michelle (2016)
In this research have been dealt with problems arising from the survival of children and adolescents, this is the way to claim support from parents through a process that ends with the sentence in which payments are available alimony and collection of the Judicial Unit of the Family, Women, Children and Adolescents then give them to mothers or guardians of them. From research conducted to mothers who charge alimony, it is noted that the money received is not invested in children and adolescents, rather on the contrary spent on issues that have nothing to do with the overall development of the real beneficiaries, in personal matters, leaving total abandonment to them. It is observed to minors working in dangerous and unsafe activities for their age, to meet their basic needs, her mother not satisfied, and not because it is not enough alimony, but poorly spent money on vanities and meet their needs, leaving total abandonment and neglect, this one without education, without clothing, without adequate food, without health and other priority needs, thereby violating the rights of their children. Thus has arisen the need to incorporate in the relevant legal framework, including monthly audits, to ensure that they invest in priority needs of children and adolescents and ensure their true integral development, as responsible adults will that justify submitting invoices investment in children, a situation that has caused a problem of a social nature, misuse of maintenance dedicating personal expenses collecting or employment in 5 luxury goods, because the check is missing and control to pensions and ensure they reach their intended recipients. Before this reality the topic and problem of instituting control and audit the management of maintenance to do the Judicial Unit of the Family, Women, Children and Adolescents who handle alimony arises then and in turn force them to restore and punish them; and we ask this audit because the money raised by the Judicial Specialized Unit of the Family, Women, Children and Adolescents through the bank becomes public money and seeking the interest of the child is favorable this audit done. I must conclude by stating that the monies collected responsible for collecting alimony give misuse, spending in vain needs them and do not invest in children, therefore the urgent need to reform the Code of Children and Adolescents to include monthly audits to present supporting demand, and ensure that they are the real beneficiaries under loe, to thereby prevent child labor and begging.